Parental compliance for speech therapy of their hearing-impaired children using cochlear implants (Journal of Fatima Jinnah Medical University, 2021)
Background: Cochlear implant is a miraculous surgery to improve hearing in profound hearing-impaired children who derive no benefit from hearing aids and consequently present with speech and language disability. This study aims to explore the parental perspective regarding compliance to speech therapy and its potential benefit in hearing-impaired children with cochlear implantation. This will help understand parental concerns and plan recommendations for providing appropriate speech therapy sessions after cochlear implantation.Subjects and methods: This cross-sectional study using purposive sampling recruited 217 parents of hearing impaired cochlear implanted children of both genders, aged 1 to 15 years. Sample was collected from Audiology Department of Riphah International University, Combined Military Hospital, Bahria Town Hospital and Alam Audiology Clinic, Lahore, Pakistan over a period of 6 months. Basic demographic sheet and self-structured questionnaire was used for data collection. SPSS Version 22 was used for data analysis.Results: Results revealed that both parents of 120 (55.3%) male and 97 (44.7%) female cochlear implanted children entered the study. A poor compliance was noted with only 88(40.55%) parents got their children consulted with a speech therapist for post implant needs and of these only 75 (84.23%) received regular speech therapy. There was significant association of those who received hearing aid trial and consultation to speech therapist (p=0.01) and length of speech therapy with regular therapy sessions (p=0.03), speech language improvement with the thought that regular speech therapy was important (p=0.04)Conclusion: By and large parents are not very compliant to speech therapy needs of their implanted children with only 40.55% consulted speech language therapists and remaining remained indifferent. Of the 40.55% who consulted speech language therapists 84.23% followed speech therapy for their children. Study also revealed a significant relationship between regular speech therapy sessions and early speech and language development.
Keywords: Hearing loss; Cochlear implant; Speech therapy